Validation of the Chinese Version of Relaxation Sensitivity Index: A Tool for Predicting Treatment Effect in Mindfulness Interventions - Zhang, Jieting; Luberto, Christina M.; Huang, Qi; Kuang, Jin; Zhong, Juan; Yeung, Albert; Zou, Liye (Frontiers in Public Health, 2021)
Background: The Relaxation Sensitivity Index (RSI) is a new measure of relaxation-related fears which was developed and validated in western samples. The RSI captures three facets of fear regarding relaxation: physical, cognitive and social concerns. This study aimed to translate and identify the factor structure of the Chinese version of the RSI. Methods: In a preliminary study, 26 items were generated mainly by translation and modified from the original RSI. In Study 1, factor analysis and internal consistency reliability analysis were conducted based on separated half samples of 597 Chinese college students. In Study 2, test-retest reliability, convergent and predictive criterion validity were examined based on 465 Chinese college students. Results: Fourteen items were selected based on the factor loading and item prevalence in the preliminary study. Factor analysis based on Study 1 identified three factors: Social appealing, Social performance and Physical concerns. In general, the RSI demonstrated good internal consistency (αs = .750 to .860), convergent validity and predictive criterion validity, while the test-retest reliability is relatively low (rs = .525 to .685). Notably, less related to the other two factors, Social performance concerns may be a unique factor solely predicting social anxiety (p < .001), but not relaxation-induced anxiety (p = .442). Conclusion: The Chinese version of the RSI possesses a factor structure different from that in the western population. The robustness of factor structure and test-retest reliability was not as good as expected. Further research is warranted to explore the validity of the RSI in Chinese samples.